Influence of Vine Vigor on Grape (Vitis vinifera L. Cv. Pinot Noir) and Wine Proanthocyanidins - Cortell, Jessica M; Halbleib, Michael; Gallagher, Andrew V; Righetti, Timothy L; Kennedy, James A (Journal of agricultural and food chemistry, 2005)
The relationships between variations in grapevine (Vitis vinifera L. cv. Pinot noir) growth and resulting fruit and wine phenolic composition were investigated. The study was conducted in a commercial vineyard consisting of the same clone, rootstock, age, and vineyard management practices. The experimental design involved monitoring soil, vine growth, yield components, and fruit composition (soluble solids, flavan-3-ol monomers, proanthocyanidins, and pigmented polymers) on a georeferenced grid pattern to assess patterns in growth and development. Vine vigor parameters (trunk cross-sectional area, average shoot length, and leaf chlorophyll) were used to delineate zones within both blocks to produce research wines to investigate the vine−fruit−wine continuum. There was no significant influence of vine vigor on the amount of proanthocyanidin per seed and only minimal differences in seed proanthocyanidin composition. However, significant increases were found in skin proanthocyanidin (mg/berry), proportion of (−)-epigallocatechin, average molecular mass of proanthocyanidins, and pigmented polymer content in fruit from zones with a reduction in vine vigor. In the wines produced from low-vigor zones, there was a large increase in the proportion of skin tannin extracted into the wine, whereas little change occurred in seed proanthocyanidin extraction. The level of pigmented polymers and proanthocyanidin molecular mass were higher in wines made from low-vigor fruit compared to wines made from high-vigor fruit, whereas the flavan-3-ol monomer concentration was lower. Keywords: Wine; phenolic; flavan-3-ols; proanthocyanidins; precision agriculture; precision viticulture; extraction; trunk cross-sectional area; shoot length; leaf chlorophyll